Sizzle reel - Greenwald, Carlyn, 1995- (Vintage Books, a division of Penguin Random House LLC, 2023)
"For aspiring cinematographer Luna Roth, coming out as bisexual at twenty-four is proving more difficult than she anticipated. Sure, her best friend and fellow queer Romy is thrilled for her-but she has no interest in coming out to her backwards parents, she wouldn't know how to flirt with a girl if one fell at her feet, and she has neither a gaydar nor a sexual history to speak of. Not to mention she really needs to focus her energy on escaping her emotionally-abusive-but-that's-Hollywood talent manager boss and actually get working under a real director of photography anyway. When she meets twenty-eight-year-old A-list actress Valeria Sullivan around the office, Luna begins to think she might just have a solution. She'll use Valeria's interest in Luna's cinematography to get a PA job on the set of Valeria's first indie-and if Valeria is as gay as Luna thinks she is, and she happens to be Luna's route to losing her virginity, too . . . well, that's just an added bonus. Enlisting Romy's help, Luna starts the juggling act of her life-impress Valeria's DP to get another job after this one (and to escape moving back in with her parents), get as close to Valeria as possible, and help Romy with her own make-it-or-break-it career moves while she's at it. But when Valeria begins to reciprocate romantic interest in Luna, the act begins to crumble along with it-straining her relationship with Romy and leaving her job prospects precarious. Now Luna has to figure out if she can she fulfill her dreams as a filmmaker, keep her best friend, and get the girl. . . or if she's destined to lose it all"--